Eksplorasi Bibliometrik tentang Perkembangan Kajian Manuskrip dan Perpustakaan di Scopus - Mufidah, Imroatul; Putri, Desiana Ekasari; Sasmita, Amira Oribia Wanda; Joko Susilo (Qurthuba: The Journal of History and Islamic Civilization, 2024)
This research aims to explore and analyze bibliometrics related to the development of manuscript and library studies in the Scopus database, related to the origin of the institutions with the most writing, the countries of origin with the most citations, annual scientific production, average citations per year and the topics most cited. often discussed. The research method used in this research is descriptive quantitative. Meanwhile, the database used in this research is Scopus and uses the R-Bibliometric Package (Biblioshiny) application to carry out data mapping and analysis. Data for 580 articles was downloaded from Scopus using the keywords "manuscript and library." Based on the data that has been processed and visualized, it is found that the British Library is the agency that has written the most on this topic. The country with the most citations is the United Kingdom. Annual scientific production during 1859-2023 experienced fluctuations and 2023 was the highest production with a total of 45 publications. The highest annual average citation was obtained at 0.7% in 2018 and there are seven mapping clusters that appeared or were discussed the most. For further research, researchers can take topics in the right quadrant, which means that the number of publications is still small and the citation rate is high. For example, library topics are related to pigment identification or history with gold.